Volcanic passive margins - Geoffroy, Laurent (Comptes rendus. Geoscience, 2005)
Compared to non-volcanic ones, volcanic passive margins mark continental break-up over a hotter mantle, probably subject to small-scale convection. They present distinctive genetic and structural features. High-rate extension of the lithosphere is associated with catastrophic mantle melting responsible for the accretion of a thick igneous crust. Distinctive structural features of volcanic margins are syn-magmatic and continentward-dipping crustal faults accommodating the seaward flexure of the igneous crust. Volcanic margins present along-axis a magmatic and tectonic segmentation with wavelength similar to adjacent slow-spreading ridges. Their 3D organisation suggests a connection between loci of mantle melting at depths and zones of strain concentration within the lithosphere. Break-up would start and propagate from localized thermally-softened lithospheric zones. These ‘soft points’ could be localized over small-scale convection cells found at the bottom of the lithosphere, where adiabatic mantle melting would specifically occur. The particular structure of the brittle crust at volcanic passive margins could be interpreted by active and sudden oceanward flow of both the unstable hot mantle and the ductile part of the lithosphere during the break-up stage.